Effects of Tobacco Products on the Nervous System - Khalimova Dilrabo Jalilovna; Umarova Maxfuza Usmonovna; Kodirova Nargizaxon Umarovna (International Journal on Orange Technologies, 2022)
Smoking is a voluntary poisoning not only of oneself, but also of others. The harm of smoking on the human body is determined primarily by the high content of harmful substances in the composition of tobacco smoke: nicotine; carbon monoxide; prussic acid; hydrogen sulfide; carbon dioxide; ammonia; pyridine bases; radioactive isotopes Since nicotine enters the human body in small doses, addiction develops, and the symptoms of acute poisoning are absent. During his life, a smoker smokes about 15 thousand lethal doses of nicotine. Smoking harms almost all organ systems.